2012
DOI: 10.1002/pbc.24121
|View full text |Cite
|
Sign up to set email alerts
|

Imatinib mesylate causes growth deceleration in pediatric patients with chronic myelogenous leukemia

Abstract: Growth in children with CML appears to be adversely impacted by imatinib therapy. BMI and IGF-1/IGFBP-3 are maintained during treatment, suggesting a direct effect of imatinib on the growth plate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
57
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 27 publications
6
57
3
Order By: Relevance
“…There was an inverse correlation between duration of imatinib therapy and the proportionate decrease in height-for-age z-scores. This study, along with other reports regarding the detrimental effect of imatinib on growth and bone metabolism, [57][58][59][60] provides further evidence that the off-target effects of imatinib must continue to be collected over longer periods of time so we can better understand how long-term continuous inhibition of c-ABL1 may impact our patients. This is particularly true for younger children treated with imatinib who may be exposed to these effects prior to puberty when they are skeletally most vulnerable.…”
Section: Late Effects Of Imatinib Therapy In Childrensupporting
confidence: 52%
“…There was an inverse correlation between duration of imatinib therapy and the proportionate decrease in height-for-age z-scores. This study, along with other reports regarding the detrimental effect of imatinib on growth and bone metabolism, [57][58][59][60] provides further evidence that the off-target effects of imatinib must continue to be collected over longer periods of time so we can better understand how long-term continuous inhibition of c-ABL1 may impact our patients. This is particularly true for younger children treated with imatinib who may be exposed to these effects prior to puberty when they are skeletally most vulnerable.…”
Section: Late Effects Of Imatinib Therapy In Childrensupporting
confidence: 52%
“…Patients with HP exposure to radiotherapy for other reasons than CNS tumors, such as acute lymphoblastic leukemia (ALL) with CNS involvement requiring CRT or historic cases where this was done prophylactically (18,19,20), diseases requiring hematopoietic stem-cell transplant (HSCT) after conditioning with total body www.eje-online.org GHD has been described in a small number of patients treated with conventional chemotherapy alone (5, 6, 7) and may also occur following treatment with targeted chemotherapy agents. Children treated for chronic myelogenous leukemia with imatinib mesylate, a TKI, may experience linear growth deceleration or arrest, but whether this side effect is related to GHD, resistance to GH or direct skeletal toxicity remains unclear (9,33,34). Ipilimumab, an anti-CTLA4 monoclonal antibody that is increasingly used to treat unresectable melanoma has been associated with hypophysitis and GHD, possibly persisting after the discontinuation of therapy (10).…”
Section: Prevalence and Risk Factorsmentioning
confidence: 99%
“…45,46 In children, various groups have reported substantial growth abnormalities associated with imatinib in children with CML. [47][48][49][50][51][52][53][54][55] There is less experience with second-and third-generation TKIs in children, but dasatinib also seems to have a similar effect on growth. 48 It appears that prepubertal children are affected more significantly, 29 and though they may experience "catch-up" growth in puberty, their final height is lower than the predicted midparental height.…”
mentioning
confidence: 99%
“…48 It appears that prepubertal children are affected more significantly, 29 and though they may experience "catch-up" growth in puberty, their final height is lower than the predicted midparental height. 47 Some reports suggest that the growth hormone/IGF-1 axis is affected by TKIs, 45,48,56,57 and cotreatment with growth hormone or recombinant IGF-1 may improve the final adult height in children receiving TKIs; however, no study has demonstrated the safety or efficacy of this strategy.…”
mentioning
confidence: 99%